The curious case of vanishing mitochondria - Karnkowska, Anna; Hampl, Vladimír (Microbial cell (Graz, Austria), 2016)
Due to their involvement in the energy metabolism, mitochondria are essential for most eukaryotic cells. Microbial eukaryotes living in low oxygen environments possess reduced forms of mitochondria, namely mitochondrion-related organelles (MROs). These do not produce ATP by oxidative phosphorylation on their membranes and some do not produce ATP at all. Still, they are indispensable because of other essential functions such as iron-sulphur (Fe-S) cluster assembly. Recently, the first microbial eukaryote with neither mitochondrion nor MRO was characterized - Monocercomonoides sp. Genome and transcriptome sequencing of Monocercomonoides revealed that it lacks all hallmark mitochondrial proteins. Crucially, the essential mitochondrial pathway for the Fe-S cluster assembly (ISC) was replaced by a bacterial sulphur mobilization (SUF) system. The discovery of such bona fide amitochondriate eukaryote broadens our knowledge about the diversity and plasticity of eukaryotic cells and provides a substantial contribution to our understanding of eukaryotic cell evolution.
Keywords: iron-sulphur cluster synthesis; mitochondrion-related organelles; amitochondriate; Monocercomonoides sp; mitochondrion